School contextualization with indigenous group’s socio-educational methods and pedagogies - Quilaqueo, Daniel; Torres, Héctor (Frontiers in Education, 2024)
This article presents a method for contextualizing school education and initial teacher training, using the case of Mapuche in schools in central-southern Chile to change the ambivalence of teaching in an indigenous context. The analysis is based on a dispositionalist-contextualist theoretical framework and the results of empirical research projects on Mapuche socio-educational knowledge. It examines the co-construction of intercultural knowledge by researchers and parents. It concludes with a Mapuche educational knowledge base that can contextualize the school curriculum and teacher training plans.